Implicit state guarantees exacerbate problem: Separated banking system alone not a solution - Benjamin Klaus; Dorothea Schäfer (DIW Economic Bulletin, 2013)
Many banks are now too big, complex, and closely interconnected to be liquidated. When they run into difficulties, they threaten the entire financial system of their economic area. Five years of financial crisis have not alleviated but exacerbated this problem. The cost of stabilizing banks is enormous, posing serious challenges to the states affected. In addition, such state guarantees create dangerously false incentives: they encourage managers and investors to engage into high risk-taking, and favor the further expansion of banks. At present, solutions are being sought in the introduction of a separated banking system, with the aim of creating smaller, less complex financial institutions that would be easier to unwind and of protecting the deposit and loan-granting part more effectively from the risks of proprietary trading. In February 2013, the German federal government presented its plans to break up German universal banks into retail and trading institutions.1 However, this article shows that under various scenarios for such a separation, many financial institutions would still exceed the size at which a bank has ever been liquidated successfully - that is, without disastrous consequences for the economy as a whole. The government proposals also envisage the deposit bank and the residual bank remaining united within a holding structure; it is questionable whether this would suffice to ensure unbundling and thus the feasibility of liquidation. The authors are therefore not convinced that the proposed legislation can achieve its declared objective of enabling the liquidation of large banks and avoiding the associated state guarantees that aggravate the problem.
Keywords: G20; 330; too-big-to-fail; structural reform; financial architecture; leverage ratio